Dual responsive Pickering emulsions stabilized by constructed core crosslinked polymer nanoparticles via reversible covalent bonds. Issue 48 (18th November 2016) - Guo, Huazhang; Yang, Duanguang; Yang, Mei; Gao, Yong; Liu, Yijiang; Li, Huaming
Abstract : Oil in water Pickering emulsions with pH- and glucose-induced rapid de-emulsification were fabricated using CCPNs constructed via DCBs as emulsifiers. Abstract : In this study, pH- and glucose-responsive Pickering emulsions stabilized by core crosslinked polymer nanoparticles, which were constructed via reversible covalent bonds, were presented for the first time. Firstly, well-defined PDMA- b -PAPBA (poly( N, N -dimethylacrylamide)- b -poly(3-acrylamidophenylboronic acid)) diblock copolymers were synthesized via sequential reversible addition–fragmentation chain transfer (RAFT) polymerization reactions. By means of complexation of PBA units of PDMA- b -PAPBA with PVA in basic water, core crosslinked polymer nanoparticles (CCPNs) with a core–shell structure were formed. The PAPBA/PVA crosslinked network and PDMA acted as the core and shell, respectively. Because of the reversible B–O chemical bonds in the core, the as-produced CCPNs showed structural transitions in response to the external stimuli involving pH and glucose. Investigation of the interfacial activities revealed that CCPNs exhibited high emulsifying performances, and oil in water (o/w) Pickering emulsions could be formed at a low particle content. The formed Pickering emulsions showed high stability at room temperature without any disturbances, whereas de-emulsification was observed upon improving the pH or adding glucose at a given pH. This is the first report on a responsive Pickering emulsion whose stability can be manipulated by glucose, and this type of fabricated manipulative Pickering emulsions are expected to provide useful guidance in the fields of oil recovery, interfacial reactions, etc .